Frequency and origin (reactive/proactive) of aggressive behavior in young people with intellectual disability and autism spectrum disorder. (4th May 2021) - Oubrahim, Leïla; Combalbert, Nicolas
Abstract : Background: The aim was to investigate the aggressive behavior of young people in specialized institutions with intellectual disability (ID) with or without autism spectrum disorder (ASD). Method: Data on 305 institutionalized young people were collected using two aggression scales, the 'Children's Scale of Hostility and Aggression: Reactive/Proactive', and the 'Behavior Problems Inventory – Short Form'. Findings: Our results show that the behavioral manifestations differ between the clinical groups (ID/ID with ASD). In addition, they reveal a decrease in all aggressive and stereotyped behaviors at 16 years in participants with ID but not in those with the dual diagnosis (ID and ASD). There would be an increase in self-injury with age in people with ID and ASD. Finally, the aggressive behaviors (verbal, relational, bullying) of people with only ID are significantly more proactive than reactive.